Influence Of Organizational Culture On Employee\'s Innovative Behaviour - Moghimi, Solmaz (2010)
The main objective of this study is to determine the influence of organizational culture on employee\'s innovative behaviour. More specifically the study looked at the different components that constitute organizational culture and examined the relationship between these components and innovative behavior. The study also determine which among the components of organizational culture could be best predictors of employees\' innovative behavior. The study involves respondents from various Malaysian organizations which performing different economic sectors.